An Ethical Approach to the Profession of Librarianship - Fatoş Subaşıoğlu (Türk Kütüphaneciliği)
The most essential features for ali professions are to determine the ethical behaviours and codes. Without these codes, a profession can not be presented and recognized. The main problem oflibrary profession in our country is that the profession has not yet be- en understood by individuals of the society. This problem can be solved by formulating professional ethical codes and agreeing upon them.